APPLICATION OF NAIVE BAYES ALGORITHM IN EDUCATIONAL GAMES LEARN TO WRITE AKSARA BALI (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Balinese script is a script from the Balinese area that was commonly used by people in ancient times to describe a word, there are many ways to keep this script sustainable and not extinct. One of them is by making a Balinese character recognition game. Which in this application the user will provide input in the form of Balinese characters written on the application, which then the input will go through a preprocessing process and then proceed with diagonal feature extraction, then the results of the feature extraction will go through a classification process using the Naïve Bayes method. The result is a web-based application that can recognize Balinese script writing using the Naïve Bayes classification method with an accuracy rate of 70.3% and get a good response from every respondent who has tested the application. Keyword : Balinese Scription, Diagonal Feature Extraction, Naïve Bayes.